Evaluation of admittance domain behavioural model complexity requirements for Power Amplifier design. Issue 12 (7th September 2022) - Moure, Maria Rocio; Casbon, Michael; Ladero, Nicolas; Fernandez‐Barciela, Monica; Tasker, Paul J.
Abstract: In the framework of Power Amplifier (PA) design for communications, frequency domain non‐linear behavioural models have shown their potential as efficient complementary modelling tools when Field Effect Transistor compact models are not available or sufficiently accurate. The Admittance behavioural model, formulated in the V‐I domain, is especially suitable for device size and fundamental frequency scaling. It is important to note that the direct extraction of this model, from the Nonlinear Vector Network Analyser (NVNA) load‐pull (LP) measurements, requires some extra processing since it necessitates a Look‐up‐Table indexed to | V 11 | rather than | A 11 |. When using such models in PA design, there is the need for the user to select the necessary model complexity. To address this requirement, in this paper, a systematic analysis methodology, to guide the user, is presented and validated in different PA design scenarios. The methodology was tested using NVNA LP measurements of GaN Heterostructure FETs. A fifth order Admittance model formulation showed good accuracy in the studied PA design scenarios.